Cost-effective pulsed laser diode transmitter for efficient laser power transfer - Yigit, Hayri; Boynuegri, Ali rifat (Optica Publishing Group, 2025)
Laser power transfer (LPT) technology is an emerging wireless power transfer technology that offers a promising way to transfer energy over long distances. The transmitter section, being a pivotal component of LPT systems, has conventionally employed continuous mode (CM) lasers. However, pulsed mode (PM) lasers have gained increasing attention due to their economic, flexible, and efficient designs. In this study, an economical and modular transmitter system is proposed for LPT applications. Through the utilization of 10 PM laser diodes, an uninterrupted power transfer capability was achieved. The results of the study showed an efficiency rate of 7.62% and a significant cost saving of $293. (c) 2025 Optica Publishing Group. All rights, including for text and data mining (TDM), Artificial Intelligence (AI) training, and similar technologies, are reserved.
Keywords: Optics